Maqasid-based Consumer Preference Index for Tawarruq Personal Financing (TPF) - Amin, Hanudin; Suhartanto, Dwi; Ghazali, Mohd Fahmi; Ali, Muhammad; Rizal, Hamid; Abdul Razak, Dzuljastri (Universitas Muhammadiyah Yogyakarta, 2022)
Relatively, maqasid al-Shariah is a missing dimension element in the available tawarruq personal financing, resulting in a convergence of this facility and its traditional counterpart. This work examines the consumer preference of tawarruq personal financing using the maqasid-based consumer preference index (MCPi). Drawing upon the MCPi, the present study examines consumer preference on the offered Tawarruq personal financing by 7 Islamic banks in Malaysia based on valid 456 usable questionnaires. The primary findings obtained indicate that all banks somewhat have a moderate MCPi. These include Bank Islam Malaysia Berhad (BIMB), Bank Muamalat Malaysia Berhad (BMMB), Maybank Islamic, CIMB Islamic, RHB Islamic, Kuwait Finance House and Al-Rajhi Bank. This study examines a new approach to measure consumer preference using the MCPi. Our contributions are confined to these particular variables – Educating Customer, Establishing Justice and Promoting Welfare. Our study also limits its perspective on the general context of tawarruq personal financing. Future works may provide different perspectives on these interrogations. This study provides a new index for Islamic banks to manage tawarruq personal financing products according to maqasid al-Shariah effectively. This study introduces a new measure of consumer preference of tawarruq personal financing namely the MCPi in the context of Malaysia.